2020
DOI: 10.1101/2020.04.12.037580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Nucleus Multiomic Profiling Reveals Age-Dynamic Regulation of Host Genes Associated with SARS-CoV-2 Infection

Abstract: 58Respiratory failure is the leading cause of COVID-19 death and disproportionately 59 impacts adults more than children. Here, we present a large-scale snATAC-seq dataset 60 (90,980 nuclei) of the human lung, generated in parallel with snRNA-seq (46,500 nuclei), 61 from healthy donors of ~30 weeks, ~3 years and ~30 years of age. Focusing on genes 62 implicated in SARS-CoV-2 cell entry, we observed an increase in the proportion of 63 alveolar epithelial cells expressing ACE2 and TMPRSS2 in adult compared to yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 83 publications
(19 reference statements)
2
32
0
Order By: Relevance
“…Human lung tissue demonstrated low levels of ACE2 expression in infants, children, and adult samples ( Fig S5). These data are broadly consistent with results of a single-nucleus RNA-seq (snRNA-seq) study of infants, children and adults up to age 30 that was reported while this manuscript was being finalized, though notably that study did not show tissue validation of their findings (16).…”
Section: Resultssupporting
confidence: 84%
“…Human lung tissue demonstrated low levels of ACE2 expression in infants, children, and adult samples ( Fig S5). These data are broadly consistent with results of a single-nucleus RNA-seq (snRNA-seq) study of infants, children and adults up to age 30 that was reported while this manuscript was being finalized, though notably that study did not show tissue validation of their findings (16).…”
Section: Resultssupporting
confidence: 84%
“…Collectively, these results consistently indicate that the human placental tissues negligibly co-express ACE2 and TMPRSS2. This reduced expression contrasts with the high expression of ACE2 and TMPRSS2 in nasal goblet and ciliated cells within the human airways, lungs, and gastrointestinal tract, which are targeted during COVID-19 [69][70][71]. Therefore, our results suggest that vertical transmission of SARS-CoV-2 is unlikely to occur unless facilitated by other concomitant pathological conditions resulting in a breach of the maternal-fetal crosstalk.…”
Section: Main Textmentioning
confidence: 62%
“…66 However, the alteration of ACE2 expression during aging is still controversial. [66][67][68] In this study, we present the first comparative single-nucleus/single-cell sequencing atlas of old versus young primate lung and cardiovascular tissues, revealing that ACE2 expression was upregulated in a both age-dependent and cell type-specific manner. The agingassociated upregulation of ACE2 was further confirmed by multiple assays, such as in-depth bulk RNA-seq, RT-qPCR, RNA-ISH, and immunostaining in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Cell types were identified according to the expression of canonical marker genes for each cluster (Supplementary information, Table S2). 31,67,85,99,100 Dimensionality reduction was performed with the "RunUMAP" function and the resultant data were visualized with the "DimPlot" function.…”
Section: Filtering Of Low-quality Cellsmentioning
confidence: 99%